2014
DOI: 10.4067/s0717-66432014000200015
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome number of two Chilean species of Nothofagus (Nothofagaceae)

Abstract: RESUMENSe documenta un número cromosómico 2n = 26 (x = 13) para Nothofagus dombeyi (Mirb.) Oerst. y N. glauca (Phil.) Krasser, el cual es similar al descrito previamente para otras especies del género. Se incrementan a 13 las especies de Nothofagus con número cromosómico conocido, existiendo dos números básicos (x = 13, 14).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
3
1
Order By: Relevance
“…Nothofagus spp. examined here are diploids with 2n = 2x = 26, which is consistent with the chromosome number reported for all species studied in Nothofagaceae so far (Armstrong & Wylie, 1965;Wardle, 1967;Ono, 1977;Carr & McPherson, 1986;Jara-Seguel et al, 2014), with the exception of N. cunninghamii (Hook.) Oerst.…”
Section: Karyotype Featuressupporting
confidence: 90%
See 3 more Smart Citations
“…Nothofagus spp. examined here are diploids with 2n = 2x = 26, which is consistent with the chromosome number reported for all species studied in Nothofagaceae so far (Armstrong & Wylie, 1965;Wardle, 1967;Ono, 1977;Carr & McPherson, 1986;Jara-Seguel et al, 2014), with the exception of N. cunninghamii (Hook.) Oerst.…”
Section: Karyotype Featuressupporting
confidence: 90%
“…Although the techniques used here are not comparable with those implemented by Ono (1977) and Jara-Seguel et al (2014), we also found that chromosomes of Nothofagus are small (< 2 µm). Notably, chromosomes of N. pumilio are of similar size to those of the other studied Nothofagus spp., contrary to observations by Ono (1977).…”
Section: Karyotype Featurescontrasting
confidence: 59%
See 2 more Smart Citations
“…First estimation for this family. Nothofagus Blume chromosome number has been reported to be very stable, with this species showing the genus' most frequent number of 2n = 26 (Jara-Seguel & al., 2014). Values of 2C including or close to the one reported here have been testified for the close families of Fagaceae, Juglandaceae or Betulaceae (Pellicer & Leitch, 2020).…”
Section: E40mentioning
confidence: 99%